Pendampingan Hukum Terhadap Masyarakat Dalam Proses Restorative Justice Di Kepolisian Resort Kupang Kota - Wewo, Jeremia Alexander; Naatonis, Mathelda (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
Restorative justice is a theory in law to close the weaknesses in resolving conventional criminal cases, namely the repressive approach as implemented in the criminal justice system. The weakness of the repressive approach as a resolution to criminal cases is, among other things, that it is oriented towards retribution in the form of punishing and imprisoning the perpetrator, but even though the perpetrator has served his sentence the victim does not feel satisfaction. This service aims to find a solution to criminal cases that can be resolved through restorative justice. As a result of the dedication, a solution was found so that the criminal case was resolved using restorative justice, firstly, there was an apology from the suspect, secondly, the victim was willing to apologize to the suspect, thirdly, the victim was willing to resolve the problem through restorative justice, fourthly, there was compensation that the suspect had to give to victims, and fifth, there is a peace agreement.